ARGUING WITH THE INCEST TABOO? THE CASE OF “DISTORTED COGNITIONS” ABOUT CHILD SEXUALITY - Janssen, Diederik F (PINS-Psychology in Society, 2025)
This paper seeks to open up critical reflection on the notion of “cognitive distortion” (CD), as applied to child sex offenders, to a broader anthropological account of children’s sexual agency, namely the arguable revitalisation and extension of incest taboos through the post-1970s rubric of child sexual abuse. Sixteen scales that purport to measure CD (1984-2009) are listed, and their gist briefly appreciated against this interpretative background. Pitting social structure against the deconstructive and disloyal crime of perversion, the pronouncement of CD shows a deep complicity to the moral status quo, namely the faithful recitation and procedural accreditation of essentially regulatory rubrics, fixtures, and truisms (“sexuality”, “sexual trauma”, “harm”, “consent”). It thus paraphrases the anthropologically expected collapse of nuance between immoral and illogical ideas at the site of social taboos, especially taboos’ contemporary predicament of ever more argumentative perverts and ever more decontextualised, and thus erratic, scientific probing. In the end, the perverts are those who, in all nuances of the expression, “don’t get it.” Circumscribing the “rationalisations, distortions, and blame shifting” of the paraphile remains the - increasingly awkward and panicked - occasion for entrenching society’s.